2016
DOI: 10.18632/oncotarget.12711
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of cancer-testis antigens in human prostate cancer

Abstract: Immune tolerance to self-antigens can limit robust anti-tumor immune responses in the use of tumor vaccines. Expression of novel tumor associated antigens can improve immune recognition and lysis of tumor cells. The cancer-testis antigen (CTA) family of proteins has been hypothesized to be an ideal class of antigens due to tumor-restricted expression, a subset of which have been found to induce antibody responses in patients with prostate disease. We demonstrate that CTA expression is highly inducible in five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…Like in other tumor models mentioned above, decitabine was also demonstrated to induce the expression of CTAs in PCa, in a synergistic combination with the HDAC inhibitor panobinostat [149]. In this study, the authors created an ex vivo culture system of PCa biopsies, which further showed inducing of CTAs, namely SSX2, in all nine cultured specimens (originating from 9 different patients).…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 70%
See 1 more Smart Citation
“…Like in other tumor models mentioned above, decitabine was also demonstrated to induce the expression of CTAs in PCa, in a synergistic combination with the HDAC inhibitor panobinostat [149]. In this study, the authors created an ex vivo culture system of PCa biopsies, which further showed inducing of CTAs, namely SSX2, in all nine cultured specimens (originating from 9 different patients).…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 70%
“…A summary of most recent studies addressing combination strategies between epigenetics and immune environment in PCa is depicted in Table 3 [108,[141][142][143][144][145][146][147][148][149][150][151][152]. Some studies have focused on epigenetic regulation of response to IFN, where both methylation and acetylation can be involved, as demonstrated by Dunn and collaborators [141].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…It has been found that TLR7 agonist (TLR7a) can be used in combination with chemotherapy, radiotherapy, and other immunotherapies to increase the immune response and to induce tumor cell apoptosis [24,25]. For example, a well-characterized TLR7 agonist R848, also called resiquimod, has been demonstrated that it works as an antitumor reagent in a mouse model of lymphoma when combined with radiation by priming antitumor immune response [26]. Our lab has previously synthesized an effective TLR7 agonist, SZU-101 [27,28], which also showed antitumor activity in a murine model of T cell lymphoma.…”
Section: Ivyspringmentioning
confidence: 99%
“…Total RNA was extracted from DAC-treated or untreated cells using Trizol reagent (Thermo Scientific, #15596026, USA) according to the 'manufacturer's instruction. RT was performed using the Reverse Transcription System (Promega, #A3500, USA) on 1 mg of total RNA, and PCR amplifications were then performed using primers shown in Table 1 [26]. Simultaneous amplification of β-actin was used as an internal control for the amount and integrity of the RNA analyzed.…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…One method to boost antigen presentation is to introduce specific point mutations in the sequence of the antigenic epitope, resulting in improved binding to MHC Class I molecules or the T-cell receptor (TCR). 138 Along these lines, the antitumor activity of a plasmid encoding mutated SSX family member 2 (SSX2; a TAA relevant for prostate carcinoma) [139][140][141] was studied in mice bearing an HLA-A2-expressing neoplasm engineered to express SSX2. Contrary to predictions, this DNA-based vaccine had limited immunostimulatory properties and poor efficacy, which was associated with increased expression of the immunosuppressive receptor programmed cell death 1 (PDCD1; best known as PD-1) on CD8 C T cells.…”
Section: Preclinical Studies -Highlightsmentioning
confidence: 99%